Testing the job demands-resources model in explaining life satisfaction of Nigerian correctional staff. Issue 5 (28th May 2022) - Lambert, Eric G.; Elechi, O. Oko; Otu, Smart
ABSTRACT: The bulk of correctional staff life satisfaction research has focused on staff in Western nations, particularly the United States. The current study examined how workplace variables are related to life satisfaction among Nigerian correctional staff, and it used the Job Demands-Resources Model as a theoretical framework. This model postulates that workplace variables can be broken into job demands and resources. Job demands are workplace variables that cause strain. Job resources are workplace variables that help staff be productive and successful and help buffer job demands. Job demands tend to be associated with negative outcomes, such as job stress, and job resources tend to be associated to positive outcomes, such as life satisfaction. Data for this study came from staff at a prison located in southeast Nigeria. The job demand variables examined were role overload and fear of victimization at work, and the job resource variables were quality of training, job autonomy, and job variety, with the outcome variable being life satisfaction. In a multivariate Ordinary Least Squares regression analysis, fear of victimization had a nonsignificant relationship with life satisfaction, role overload had a negative relationship, and quality training, job autonomy, and job variety each had a positive associations.